A Validation Process for Underwater Localization Algorithms. (1st September 2014) - Hildebrandt, Marc; Gaudig, Christopher; Christensen, Leif; Natarajan, Sankaranarayanan; Carrio, Javier Hidalgo; Paranhos, Patrick Merz; Kirchner, Frank
This paper describes the validation process of a localization algorithm for underwater vehicles. In order to develop new localization algorithms, it is essential to characterize them with regard to their accuracy, long-term stability and robustness to external sources of noise. This is only possible if a gold-standard reference localization (GSRL) is available against which any new localization algorithm (NLA) can be tested. This process requires a vehicle which carries all the required sensor and processing systems for both the GSRL and the NLA. This paper will show the necessity of such a validation process, briefly sketch the test vehicle and its capabilities, describe the challenges in computing the localizations of both the GSRL and the NLA simultaneously for comparison, and conclude with experimental data of real-world trials.